Problem Based Learning Model Design, Using Capcut Application in SKI Learning to Improve Learning Outcomes of Class X Students of MAN 1 Majene - Nurfitrayadi; Usman; Abdul Halik; Ambo Dalle; Ahdar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to develop and test the effectiveness of a problem-based learning model (Problem Based Learning) using the CapCut application in learning Islamic Cultural History (SKI) for class X students at MAN 1 Majene. The research method used is experimental research. The research instruments used are learning outcomes tests and student response questionnaires. The data obtained was analyzed using quantitative descriptive analysis techniques. The main instrument of this research is a test supported by research instruments with data collection in the form of documentation, with a research sample of 53 people divided into 2 groups, namely a sample of 27 people as the control group and 26 people as the experimental group. The sampling technique used is the sampling technique. The research results show that the Problem Based Learning model using the CapCut application is effective in improving student learning outcomes in SKI subjects. This can be seen from the analysis results showing that the value of O1 is smaller than O2, so the X received is (80.00 > 78.00). The experimental class used an Android cellphone with a pre-test score of 80.22 and an average post-test score of 82.22, while the average score of the pre-test control class was 80.00 and the average post-test score was 81.46. Thus, it is proven that the Problem Based Learning Model, Using the CapCut Application in SKI Learning, Improves Class X Student Learning Outcomes. The implication of this research is that the integration of technology in learning can improve the quality of learning and student learning outcomes in the context of SKI learning at MAN 1 Majene.